Success of rechallenging dabrafenib and trametinib combination therapy after trametinib-induced rhabdomyolysis: a case report. Issue 2 (April 2018) - Muto, Yusuke; Ng, William; Namikawa, Kenjiro; Takahashi, Akira; Tsutsumida, Arata; Nishida, Makiko; Yamazaki, Naoya
Abstract : The mitogen-activated protein kinase pathway regulates cell growth and differentiation and is activated by BRAF mutations. BRAF mutations are present in about 40–50% of cutaneous melanomas. More than 90% of BRAF mutations are the V600E type. BRAF inhibitor (dabrafenib or vemurafenib) and MEK inhibitor (trametinib or cobimetinib) combination therapies are effective for BRAF-mutant advanced melanomas. A variety of side effects have been observed with combination therapy including pyrexia, fatigue, nausea, and vomiting. Rhabdomyolysis is one of the most severe adverse events, but it is very rare. Only two cases of rhabdomyolysis have been reported in clinical trials. A 41-year-old Japanese woman with cutaneous melanoma was started on a combination of dabrafenib and trametinib therapy after failure of immune checkpoint therapy. One month later, she complained of myalgia and fatigue and was shifted to our hospital. She was diagnosed with trametinib-induced rhabdomyolysis and showed improvement only with a high volume of fluid infusion. We stopped combination therapy, but there were no useful treatment options for her. After resuming dabrafenib, followed by trametinib, she did not have any problems. This is the first case of a patient with metastatic cutaneous melanoma who could recommence combination therapy after trametinib-associated rhabdomyolysis. We assume that not all patients experience recurrence of rhabdomyolysis in trametinib-induced rhabdomyolysis. As few cases have been reported, more information is needed. We have to evaluate safety carefully if rechallenging combination therapy.